2021
DOI: 10.4018/978-1-7998-7537-6.ch007
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Followers in Higher Education During a Pandemic

Abstract: The campus community was notified that classes were cancelled leading up to spring break due to COVID-19. Aggressive preparations for remote teaching began taking shape for the time when classes would resume. This chapter delves into leader/follower dynamics among faculty-student and student-student relationships. Examples describing how faculty accomplished the task of addressing some of these issues from a leader/follower relationship perspective will be an additional focus in this chapter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Establishments such as higher education institutions are well positioned to understand and address disparities in representation. They also have a unique role to play in equity and upward mobility by addressing institutional policies and practices that have historically reinforced deep-seated racism within professional fields, programs and systems in the USA (Garibay and Vincent, 2016;Lederman, 2021). Although past literature suggests demographic and socioeconomic factors may influence students' perceptions of sustainability (Aina, 2019), little to no published research could be found assessing how perceptions influence diverse students' participation in campus sustainability programs.…”
Section: Introductionmentioning
confidence: 99%
“…Establishments such as higher education institutions are well positioned to understand and address disparities in representation. They also have a unique role to play in equity and upward mobility by addressing institutional policies and practices that have historically reinforced deep-seated racism within professional fields, programs and systems in the USA (Garibay and Vincent, 2016;Lederman, 2021). Although past literature suggests demographic and socioeconomic factors may influence students' perceptions of sustainability (Aina, 2019), little to no published research could be found assessing how perceptions influence diverse students' participation in campus sustainability programs.…”
Section: Introductionmentioning
confidence: 99%